Effects of extrusion parameters on the mechanical properties of aluminum - Karahan, İsmail. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
The effects of some extrusion parameters, extrusion ratio and initial billet temperature, on the structure and mechanical properties of aluminum are examined. Initial billet temperature and extrusion ratio determine the structural changes occuring during and after the extrusion process and their contribution to the structure of the product. It is noted that mechanical properties of product also change with these parameters via the structure. Extrusion ratio effects are recognized in the strain rate which is, then combined with temperature effects in a temperature corrected strain rate term, Z. It is shown that structure and mechanical properties of product are related to, and can be controlled by, Z. Relations between the logarithm of Z and mechanical properties of product are used to develope the extrusion limit diagram so that it shows the mechanical properties of extruded product.
Keywords: Aluminum.; Aluminum -- Extrusion.; Metals -- Extrusion.